2014
DOI: 10.1002/dvdy.24156
|View full text |Cite
|
Sign up to set email alerts
|

The chromatin remodeling protein CHD7, mutated in CHARGE syndrome, is necessary for proper craniofacial and tracheal development

Abstract: Background Heterozygous mutations in the chromatin remodeling gene CHD7 cause CHARGE syndrome, a developmental disorder with variable craniofacial dysmorphisms and respiratory difficulties. The molecular etiologies of these malformations are not well understood. Homozygous Chd7 null mice die by E11, whereas Chd7Gt/+ heterozygous null mice are a viable and excellent model of CHARGE. We explored skeletal phenotypes in Chd7Gt/+ and Chd7 conditional knockout mice, using Foxg1-Cre to delete Chd7 (Foxg1-CKO) in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 48 publications
4
41
1
Order By: Relevance
“…Chd7 results in craniofacial abnormalities, cardiac defects were not reported (Sperry et al, 2014). This agrees with the genetic rescue experiments of Randall et al (2009).…”
Section: Tissue Specific Requirements For Chd7supporting
confidence: 88%
“…Chd7 results in craniofacial abnormalities, cardiac defects were not reported (Sperry et al, 2014). This agrees with the genetic rescue experiments of Randall et al (2009).…”
Section: Tissue Specific Requirements For Chd7supporting
confidence: 88%
“…Ikaros-NuRD subunit CHD4 has a role in thymocyte development (Arenzana et al, 2015;Sridharan and Smale, 2007) NuRD has roles in cardiomyocyte proliferation (Garnatz et al, 2014) and in renal progenitor cells during kidney development (Denner and Rauchman, 2013) CHD5 CHD5 Orchestrates chromatin remodeling during neurogenesis (Thompson et al, 2003;Vestin and Mills, 2013) and sperm development ) CHD7 CHD7 Involved in charge syndrome (Bajpai et al, 2010;Janssen et al, 2012;Vissers et al, 2004), neurogenesis (Hurd et al, 2010), adult brain development (Jones et al, 2015), cardiac development (Payne et al, 2015), and proper craniofacial and tracheal development (Sperry et al, 2014) CHD8 CHD8 Involved in autism spectrum disorder (Sanders, 2015) and neural development (Bernier et al, 2014;Cotney et al, 2015;Sugathan et al, 2014) CHD9 CHD9 Associates with selective promoters of osteoprogenitors (Shur et al, 2006) *Current mouse gene symbols are listed only where they differ from protein nomenclature.…”
Section: Developmental Roles Of Chd Complexesmentioning
confidence: 99%
“…In humans, CHD7 is mutated in patients with CHARGE syndrome, which is characterized by neural, craniofacial, ear, eye and heart defects (Janssen et al, 2012;Vissers et al, 2004). The morpholino-mediated downregulation of Chd7 in Xenopus embryos recapitulates most CHARGE syndrome symptoms (Bajpai et al, 2010) and the conditional deletion of Chd7 in mice also recapitulates these symptoms (Sperry et al, 2014). CHD7 is also required for the formation and migration of neural crest cells (Bajpai et al, 2010), which contribute to the development of craniofacial, peripheral nervous system and heart (Fig.…”
Section: Developmental Roles Of Chd Complexesmentioning
confidence: 99%
“…Sperry et al (2014) found several phenotypic features that are well‐known in humans with CHARGE syndrome in Foxg1 and Wnt1 conditional knockout mice, but they also observed skull bone abnormalities such as frontal, parietal and occipital bone dysplasia and hypoplasia of the maxilla (Sperry et al, 2014). The same abnormalities were not seen in heterozygous Chd7 mice and have not been described in humans, but as described above, clivus and petrosal abnormalities are common in individuals with CHARGE syndrome.…”
Section: Research and Cranial Imagingmentioning
confidence: 99%